2015
DOI: 10.1016/j.jaci.2015.03.033
|View full text |Cite
|
Sign up to set email alerts
|

CCCTC-binding factor controls the homeostatic maintenance and migration of Langerhans cells

Abstract: Our results show that CTCF positively regulates the homeostatic pool and the efficient emigration of LCs, which are required for modulating the functional immune network of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 75 publications
0
28
1
Order By: Relevance
“…Isolation and flow cytometric characterization of DC subsets was performed according to our previous work and other studies as indicated in the Supplementary Materials (Guilliams et al, 2016;Kim et al, 2015;Tamoutounour et al, 2013).…”
Section: Cell Isolation and Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and flow cytometric characterization of DC subsets was performed according to our previous work and other studies as indicated in the Supplementary Materials (Guilliams et al, 2016;Kim et al, 2015;Tamoutounour et al, 2013).…”
Section: Cell Isolation and Flow Cytometrymentioning
confidence: 99%
“…Pre-cDCs from CD45.2 þ BM were determined and sorted as described in our previous study (Kim et al, 2015). Total 2 Â 10 6 CD45.1 þ supporting BM cells and 1 Â 10 4 sorted CD45.2 þ pre-cDCs were gently mixed and cultured in the complete RPMI medium containing FLT3L-conditioned supernatant with or without additional GM-CSF supplement.…”
Section: Pre-cdc Sorting and Mixed Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of skin tissues was done according to our previous studies [31,32]. Briefly, excised skin was digested in 2.5 mg/ml dispase II (Roche, GmbH, Mannheim, Germany) to separate epidermal and dermal sheet.…”
Section: Tissue Preparation and Flow Cytometrymentioning
confidence: 99%
“…20 Among them, CCCTC binding factor (CTCF) can promote the outflow of LCs from the epidermis. 34 CTCF plays a variety of roles in the haematopoietic lineage, which can regulate the early development of thymocytes and participate in the development and the operation of macrophages. 35,36 Gr-1 (also known as Ly-6c/G) is a monocyte with high expression of monocyte markers, and it is the precursor of LC in inflammatory epidermis.…”
Section: Mig R Ation Of L Ang Erhans Cell S During Homeos Ta S Is Amentioning
confidence: 99%